2008
DOI: 10.1063/1.2838345
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of structural, elastic, and electronic properties of chromium carbides

Abstract: Using first-principles calculations, we systematically studied the structural, elastic, and electronic properties of the technologically important chromium carbides: Cr3C2, Cr7C3, Cr23C6, Cr3C, and CrC. Our calculations show that the ground state structure for Cr7C3 is hexagonal, not orthorhombic. We further predict WC to be the energetically most stable structure for CrC. Our results indicate that all chromium carbides considered in this study are metallic and mechanically stable under the ambient condition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(50 citation statements)
references
References 22 publications
7
43
0
Order By: Relevance
“…), which are of great technological importance, are not very clear. Therefore, theoretical studies on the basic properties of materials have been performed [17][18][19][20][21][22][23][24]. Music et al [17] have applied the first-principles calculations to study the electronic and mechanical properties of Cr 7 C 3 by using an orthorhombic cell; they found covalent-ionic Cr-C-Cr chains in a metallic matrix; the estimated bulk modulus and Young modulus values are 309 and 371 GPa, respectively.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…), which are of great technological importance, are not very clear. Therefore, theoretical studies on the basic properties of materials have been performed [17][18][19][20][21][22][23][24]. Music et al [17] have applied the first-principles calculations to study the electronic and mechanical properties of Cr 7 C 3 by using an orthorhombic cell; they found covalent-ionic Cr-C-Cr chains in a metallic matrix; the estimated bulk modulus and Young modulus values are 309 and 371 GPa, respectively.…”
Section: Introductionmentioning
confidence: 98%
“…Zhou et al [21] calculated the elastic properties and electronic structures of several Cr doped Fe 3 C compounds using first-principles method and concluded that Cr 3 C is the most stable structure among four (Fe, Cr) 3 C structures (Fe 3 C, Fe 11 Cr 1 C 4 , Fe 10 Cr 2 C 4 and Cr 3 C), but they are less stable than Cr 3 C 2 , Cr 7 C 3 and Cr 23 C 6 . Lately, Jiang [22] studied the structural, elastic, and electronic properties of chromium carbides by first-principles calculations; by providing a set of elastic constants for the first time, he found WC-type CrC is a potential low-compressibility and hard material with the highest bulk and shear moduli and the lowest Poisson's ratio. However, to the best of our knowledge, the theoretical hardness, and elastic anisotropy indexes of chromium carbides have not yet been discussed systematically in literatures.…”
Section: Introductionmentioning
confidence: 99%
“…It was also assumed that the carbide precipitate M 23 C 6 had a cube-cube orientation relationship with the parent austenite grain [22,26,54]. The material properties ( Table 2) that are used are representative of low-carbon martensitic steel and carbide precipitates M 23 C 6 [55]. It was assumed here that the M element is chromium.…”
Section: Resultsmentioning
confidence: 99%
“…For an orthorhombic structure like the Pt 2 Mo-type Ni 2 Cr 1Àx Mo x , the criteria of mechanical stability can be described as [28][29][30]:…”
Section: Resultsmentioning
confidence: 99%